2022
DOI: 10.1155/2022/6216232
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of Teaching Mode of Film and TV Art in Institution of Higher Learning Using Virtual Simulation Technology

Abstract: The modernization of education necessitates the enhancement of instructional quality. This paper begins with a basic overview of the current state of film and television art education and then goes on to examine the current state of film and television art education and develop a virtual simulation-based teaching mode for film and television art. This paper develops an instructional quality evaluation model to assess the feasibility of this teaching mode. In this model, GA is used to optimize BPNN's initial we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Individualized learning can meet the individual needs and differences of students, stimulate their learning motivation and interest; Collaborative learning can provide opportunities for interaction and collaboration among students, promoting knowledge co construction and deep understanding [7][8][9] .…”
Section: Exploring New Learning Paradigms Based On Personalized Learn...mentioning
confidence: 99%
“…Individualized learning can meet the individual needs and differences of students, stimulate their learning motivation and interest; Collaborative learning can provide opportunities for interaction and collaboration among students, promoting knowledge co construction and deep understanding [7][8][9] .…”
Section: Exploring New Learning Paradigms Based On Personalized Learn...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%